Spillovers from Systemic Bank Defaults - Mark Mink; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2014)
We examine to what extent banks' stock market values during the 2007-2012 financial crisis were driven by increases in the default risk of banks designated as globally systemically important by the Financial Stability Board. We find that bank market values hardly respond to changes in the default risk of individual systemic banks. Together, however, changes in systemic banks' default risk explain a substantial part of changes in other banks' market values. This result is robust across several sub-samples, using both credit default swap spreads and Moody's expected default frequencies as indicators of default risk.
Keywords: G01; G15; G21; G28; 330; systemic banks; spillovers; global financial crisis; financial regulation